2006
DOI: 10.1007/s11270-006-2816-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemistry of Waters of Volcanic Rocks: The Case of The Volcanosedimentary Rocks of Thrace, Greece

Abstract: Abstract. This work is referred to the characterization of the environmental hydrochemistry in the broader Sapes area -Thrace region, on the basis of physico-chemical properties of surface and groundwaters occurring in the volcanosedimentary formations of this area, where gold mining activities are planned to operate. Volcanic rocks are considerably altered where they are in contact with hydrothermal solutions. Aquifers are formed within these formations. Surface and ground waters are strongly metalliferous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The composition analysis showed that the mineral structure already contains Cd, Cu, Pb, and Zn ( Table 2). The presence of heavy metals in volcanic rock has also been reported by Petalas et al (2006) who studied the hydrochemistry of waters of volcanic rocks. They found the following order of dominance for the heavy metals in surface and ground waters: Fe> Mn>Zn>Ni>Cu.…”
Section: Theoretical Background On Adsorption Isothermsmentioning
confidence: 58%
“…The composition analysis showed that the mineral structure already contains Cd, Cu, Pb, and Zn ( Table 2). The presence of heavy metals in volcanic rock has also been reported by Petalas et al (2006) who studied the hydrochemistry of waters of volcanic rocks. They found the following order of dominance for the heavy metals in surface and ground waters: Fe> Mn>Zn>Ni>Cu.…”
Section: Theoretical Background On Adsorption Isothermsmentioning
confidence: 58%
“…Generally, HCO 3 − concentration in right bank tributaries was moderate except a higher concentration at AR and SI. HCO 3 − comes mainly from carbonate weathering contributed by oxidation of organic carbon (Petalas et al 2006;Arumugam and Elangovan 2009). In addition, the moderate concentration of HCO 3 − particularly around upstream is associated with the streams dominantly fed by glacier and snow melt in carbonate lithology.…”
Section: Water Chemistrymentioning
confidence: 99%
“…Sulphur in reduced or oxidized form may be volatilized and released in large amounts in volcanic regions and can be present in geothermal water as well. As shown in Figure 12 higher sulphate concentrations of groundwater are related to lower pH values (Petalas et al, 2006). The dissolution of the sulphide minerals creates acid groundwater that could attack feldspars and release Na C into solution (Rosen and Jones, 1998).…”
Section: Groundwater Hydrogeochemistrymentioning
confidence: 99%